Taconic Metamorphism Preserved in the Baie Verte Peninsula, Newfoundland Appalachians: Geochronological Evidence for Ophiolite Obduction and Subduction and Exhumation of the Leading Edge of the Laurentian (Humber) Margin During Closure of the Taconic Seaw - Castonguay, Sébastien; van Staal, Cees R.; Joyce, Nancy; Skulski, Thomas; Hibbard, James P. (Geoscience Canada, 2014)
The Baie Verte Peninsula, western Newfoundland Appalachians, preserves evidence for Early to Mid Ordovician closure of the Taconic seaway, which led to obduction of the Baie Verte oceanic tract (BVOT) ophiolites onto the Laurentian (Humber) margin and Taconic orogenesis. The scarcity of Taconic radiometric ages (and predominance of Silurian (Salinic) data) from the Humber margin rocks (down-going plate) has been problematic, calling into question the intensity and existence of Taconic collisional orogenesis. 40Ar/39Ar and in situ U–Pb geochronology was undertaken on metamorphosed units from the Laurentian basement (Mesoproterozoic East Pond Metamorphic Suite), from the ca. 560 Ma Birchy Complex forming the leading edge of the Humber margin, and from the ca. 490 Ma ophiolitic rocks of the BVOT (Advocate Complex) in order to address this question. Our results confirm evidence of Taconic metamorphism along the Humber margin and at the base of the ophiolites. Ages obtained from the structural base of the Advocate Complex (481–465 Ma) are interpreted to reflect the timing of accretion and internal thickening of the ophiolite, whereas data from the underlying Birchy Complex (467–461 Ma) record the underthrusting and exhumation of the leading edge of the Humber margin along a subduction channel, penecontemporaneously with final obduction of the BVOT. A concordant ca. 465 Ma zircon age and REE data obtained from retrogressed eclogite of the East Pond Metamorphic Suite suggest that the parautochthonous Humber margin was locally subducted to eclogite-facies conditions during the Taconic collision and partly exhumed to amphibolite-facies conditions prior to a strong Silurian (Salinic) tectonometamorphic overprint.